2013
DOI: 10.17129/botsci.5
|View full text |Cite
|
Sign up to set email alerts
|

Los jardines botánicos y la crisis de la biodiversidad

Abstract: Resumen: Históricamente, los jardines botánicos se enfocaban sobre especies con interés económico, y no había mención alguna de la conservación hasta mediados del siglo XX. La destrucción de las selvas y bosques, pérdida de biodiversidad y el cambio climático son problemas reales y los jardines botánicos modernos desarrollaron estrategias para enfrentarlos; la conservación ex situ e in situ, y una alianza de jardínes botánicos para la restauración ecológica. Los jardines botánicos cumplieron ocho de las 16 met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
0
6
0
5
Order By: Relevance
“…6. The establishment of ex situ collections and monitoring of species reproduction and germination/propagation after disturbances, both natural and human induced, as indicated by Vovides et al (2010); Calonje et al (2011); Vovides et al (2013); Griffith et al (2015); and Griffith et al (2017) for Zamia species. The implementation of in situ and ex situ collections and germplasm banks linked to botanical gardens are useful to promote the value of tropical cycads and may stimulate scientific and educational research aimed at the conservation of the group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6. The establishment of ex situ collections and monitoring of species reproduction and germination/propagation after disturbances, both natural and human induced, as indicated by Vovides et al (2010); Calonje et al (2011); Vovides et al (2013); Griffith et al (2015); and Griffith et al (2017) for Zamia species. The implementation of in situ and ex situ collections and germplasm banks linked to botanical gardens are useful to promote the value of tropical cycads and may stimulate scientific and educational research aimed at the conservation of the group.…”
Section: Discussionmentioning
confidence: 99%
“…Mexico is also an exception regarding action plans for conservation. The country has developed local conservation actions based on national collections, botanical gardens, investing in sustainable use of cycad species by means of educational programs (Donaldson, 2003;La´zaro-Zermeño, Gonza´lez-Espinosa, Mendoza, & Mart ınez-Ramos, 2011;Pe´rez-Farrera, Quintana-Ascencio, Salvatierra, & Vovides, 2000;Vovides, Iglesias, Luna, & Balca´zar, 2013;Vite, Pulido & Va´zquez, 2013). Following this example, Australia and South Africa have also increased the number of cycad related studies (FDS).…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that the best represented plant groups in our collection are Orchidaceae and Zamiaceae. As a result, JBC has almost 50% of Mexican cloud forest orchids and has the most important Cycad collection in Mexico and perhaps in Latin America (Vovides et al, 2014). Caballero et al (2012) reported that the Instituto de Biología Botanic Garden (Mexico City, Mexico), The Botanic Garden "Xiitbal Neek" (Yucatán, Mexico) and the JBC were the top three Mexican botanic gardens with most documented species held in their collections (1122, 1037, and 743 species, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Todas estas colecciones están al servicio de estudiantes, semilleros y grupos de investigación, así como de expertos y comunidades científicas, y por supuesto de cualquier ciudadano. Si bien la conservación in situ y ex situ que tienen los Jardines Botánicos, son necesarias, es importante decir que las primeras favorecen el mantenimiento de una gran cantidad de muestras, mientras que en las segundas, las muestras son limitadas, y pueden presentarse cambios impredecibles (Vovides et al, 2013).…”
Section: Preservación Y Conservación Los Jardinesunclassified